How South Korea's waste management system becomes a model for the world: What Indonesia can learn from South Korea's experience - Yumitro, Gonda; Oktaviani, Sukma; Deniar, Shannaz Mutiara (Communications in Humanities and Social Sciences, 2024)
This article explores South Korea's waste management system, focusing on effective food waste management, a key factor contributing to the country's overall success in waste management. The effectiveness of the South Korean system has made it a case study model for government officials in other countries. This article uses qualitative methods, relying on journal references from the Scopus database, with additional references obtained through Harzing's Publish or Perish. The data analysis was conducted using VOSviewer, an application designed to visualize keywords across all the compiled references. The findings show that South Korea's renowned efficient waste management system focuses on key aspects such as Government Initiatives, Waste Segregation, Pay-as-You-Throw System, Recycling Facilities, Waste-to-Energy Plants, Public Awareness and Education, as well as Enforcement and Penalties. Indonesia needs to explore and adopt several initiatives and strategies for efficiently managing various types of waste. This imperative arises particularly in light of the UNEP Food Waste Index 2021 report, which reveals that Indonesia has emerged as the Southeast Asian country with the highest food waste production.